The impact of dental restorations’ quality on caries risk - Rendeniece I. (SHS Web of Conferences, 2012)
The purpose of this study was to evaluate how the quality of government funded restorations can impact caries prevalence. After randomisation, One hundred thirty five (135) 12–13-year-old children were examined in the Gulbene municipality of Latvia and 175 restorations placed in premolars or second molars were evaluated. It was concluded that the quality of restorations made by publicly funded dentistry is low, which could be a reason for secondary caries and other complications and results in greater expenses in the future.